The effect of Kegel exercises on pain, urinary incontinence and strength of pelvic floor muscles in women with stress urinary incontinence and back pain - Mozhghan Goodarzi Nasab; Seyed Sadrodin Shojaodin; Mohammad Hosein Naser Melli (Mashhad University of Medical Sciences, 2021)
Introduction: Stress urinary incontinence is a common problem among adults in the community and is more frequent in women. Its incidence increases with increasing age, the number of pregnancy and body mass index (BMI). Exercise therapy has an important role in the treatment of stress urinary incontinence. Therefore, this study was performed with aim to evaluate the effect of Kegel exercises on pain, urinary incontinence and strength of pelvic floor muscles in women with stress urinary incontinence and back pain. Methods: This quasi-experimental study was performed in 2019 on 30 women with stress urinary incontinence and low back pain in the age range of 35-50 years. The subjects were placed in two equal groups of 15 experimental and control. In order to evaluate the pain, urinary incontinence, urinary incontinence diagnosis form and the pelvic floor muscle strength, the Visual Analogue Scale, and Oxford Form were used, respectively. The experimental group performed Kegel exercises for eight weeks (3 sessions of 30 to 45 minutes per week). Data were analyzed by SPSS software (version 22) and Shapiro wilk, Leven, paired t-test and one-way analysis of covariance. P<0.05 was considered statistically significant. Results: The findings of the present study showed that eight weeks of kegel exercises reduced pain, urinary incontinence and increased pelvic floor muscle strength in women with stress urinary incontinence and back pain in the experimental group compared to the control group (P≤0.05). Conclusion: Kegel exercises reduce pain, urinary incontinence and increase strength of pelvic floor muscles in women with stress urinary incontinence and back pain, so it is recommended as a non-invasive and low cost intervention to control urinary incontinence.